Evaluation of the Good Way model : a treatment approach for young people with harmful sexual behaviour : a thesis presented in partial fulfilment of the requirements for the degree of Doctorate in Clinical Psychology, Massey University, Auckland, New Zealand - Weedon, Victoria (Massey University, 2015)
Adolescents with harmful sexual behaviour (HSB) have been identified as perpetrating a significant amount of child sexual abuse, and while treatment programmes have become more available, evaluation studies of these have lagged far behind. The primary aim of the research reported in this thesis was to evaluate the effectiveness of the Good Way model (GWM) intervention developed by Ayland and West (2006) for adolescent boys undergoing treatment for HSB. The GWM is advanced as a strengths-- based cognitive behavioural approach which meets recommended key programme priorities for the treatment of youth with HSB. This study examined the effectiveness of the GWM within two community--based treatment programmes in New Zealand: WellStop, which is based in Wellington; and STOP, which is based in Christchurch. The participants were 12 male youths aged between 11 and 17 years and their families. Five participants were intellectually disabled. The study was carried out over a three-- year period and by the end of the study, nine participants had completed treatment, two remained in treatment, and one had dropped out due to the impact of unstable placements. The average treatment length was 7.5 months. Treatment effectiveness was examined within a multiple--baseline design framework. In this study the magnitude of experimental change was largely established via visual analysis, the percentage of data points exceeding the median (PEM), and Cohen’s d. The results imply a functional relationship between GWM treatment and the reduction of HSB and an increase in positively occurring behaviours related to strengths and resiliency. Positive results were obtained from measures focusing on outcome and therapeutic alliance. There was also evidence for change in individual participants across measures of internalising--type problems. Overall, the findings indicate that the introduction of the GWM intervention targeted the problem behaviour appropriately and that it was well received by participants.
Keywords: Teenage sex offenders; Rehabilitation; New Zealand